Validity of a family-centered approach for assessing infants' social-emotional wellbeing and their developmental context: a prospective cohort study - Margriet Hielkema; Andrea F. De Winter; Sijmen A. Reijneveld (BMC, 2017)
Abstract Background Family-centered care seems promising in preventive pediatrics, but evidence is lacking as to whether this type of care is also valid as a means to identify risks to infants' social-emotional development. We aimed to examine the validity of such a family-centered approach. Methods We conducted a prospective cohort study. During routine well-child visits (2-15 months), Preventive Child Healthcare (PCH) professionals used a family-centered approach, assessing domains as parents' competence, role of the partner, social support, barriers within the care-giving context, and child's wellbeing for 2976 children as protective, indistinct or a risk. If, based on the overall assessment (the families were labeled as "cases", N = 87), an intervention was considered necessary, parents filled in validated questionnaires covering the aforementioned domains. These questionnaires served as gold standards. For each case, two controls, matched by child-age and gender, also filled in questionnaires (N = 172). We compared PCH professionals' assessments with the parent-reported gold standards. Moreover, we evaluated which domain mostly contributed to the overall assessment. Results Spearman's rank correlation coefficients between PCH professionals' assessments and gold standards were overall reasonable (Spearman's rho 0.17-0.39) except for the domain barriers within the care-giving context. Scores on gold standards were significantly higher when PCH assessments were rated as "at risk" (overall and per domain).We found reasonable to excellent agreement regarding the absence of risk factors (negative agreement rate: 0.40-0.98), but lower agreement regarding the presence of risk factors (positive agreement rate: 0.00-0.67). An "at risk" assessment for the domain Barriers or life events within the care-giving context contributed most to being overall at risk, i.e. a case, odds ratio 100.1, 95%-confidence interval: 22.6 - infinity. Conclusion Findings partially support the convergent validity of a family-centered approach in well-child care to assess infants' social-emotional wellbeing and their developmental context. Agreement was reasonable to excellent regarding protective factors, but lower regarding risk factors. Trial registration Netherlands Trialregister, NTR2681. Date of registration: 05-01-2011, URL: http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=2681 .